2018
DOI: 10.1124/mol.118.113423
|View full text |Cite
|
Sign up to set email alerts
|

The 5′-AMP-Activated Protein Kinase Regulates the Function and Expression of Human Organic Anion Transporting Polypeptide 1A2

Abstract: The organic anion transporting polypeptides (OATPs) are important membrane proteins that mediate the cellular uptake of drugs and endogenous substances. OATP1A2 is widely distributed in many human tissues that are targeted in drug therapy; defective OATP1A2 leads to altered drug disposition influencing therapeutic outcomes. 59-AMP-activated protein kinase (AMPK) signaling plays an important role in the pathogenesis of the metabolic syndrome characterized by an increased incidence of type II diabetes and nonalc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In our cohort, the presence of CA variant in SLCO1A2 rs11568563 has been strongly associated with a lower risk of DM2 incidence. These results reinforce the observations supporting the idea that gene variants in SLCO1A2 could be involved in the pathogenesis of metabolic syndrome, characterized by an increased incidence of DM2 [33].…”
Section: Discussionsupporting
confidence: 90%
“…In our cohort, the presence of CA variant in SLCO1A2 rs11568563 has been strongly associated with a lower risk of DM2 incidence. These results reinforce the observations supporting the idea that gene variants in SLCO1A2 could be involved in the pathogenesis of metabolic syndrome, characterized by an increased incidence of DM2 [33].…”
Section: Discussionsupporting
confidence: 90%
“…Interestingly, CK2 is reported to be dysregulated in many disease states, including breast cancer, in which the OATP1A2 level was elevated (42,137). Another study showed that OATP1A2 trafficking is regulated by 5'-AMP-activated protein kinase (AMPK) signaling associated with an increased incidence of type II diabetes and nonalcoholic fatty liver disease (138). Further investigations will be necessary to assess how and to what extent these multiple kinases are connected and contribute to the processing of the functional OATP1A2 in healthy and disease states.…”
Section: Oatp1a2mentioning
confidence: 99%
“…OATP1A2 dysfunction may damage the pharmacokinetics and traits of a drug, thereby affecting the effectiveness of the treatment, and it may also hinder the absorption of endogenous organisms to the target tissue ( 43 ). OATP1A2 is regulated by AMPK, which has an impact on its membrane target, internalization, reuse, and degradation processes ( 44 ). Some researchers found that OATP1A2 could not be detected in the large intestine of normal controls when conducting intestinal transport protein research, but in another study, OATP1A2 was found to be widely expressed in patients with CRC liver metastases ( 45 , 46 ).…”
Section: Discussionmentioning
confidence: 99%